Methods in Language Documentation and Description: A Guide to the Kelabit Documentation Project - Charlotte Hemmings (Journal of Modern Languages)
Kelabit is a Western Austronesian language spoken in Northern Sarawak, Malaysia. This paper provides a guide to the Kelabit documentation project, contextualising the materials collected, and discussing the research methods used. It is hoped that this will make the project outputs more accessible and provide a useful reference for researchers and communities looking to document similar phenomena in related languages.